The Impact of Endoscopic Ultrasound Findings on Clinical Decision-making in Barrett's Esophagus with High-Grade Dysplasia or Early Esophageal Adenocarcinoma - Bulsiewicz, William J. (Dis Esophagus, 2012)
BACKGROUND & AIMS: The clinical utility of endoscopic ultrasound (EUS) for staging patients with Barrett's esophagus (BE) and high-grade dysplasia (HGD) or intramucosal carcinoma (IMC) prior to endoscopic therapy is unclear. METHODS: Retrospective analysis of patients with HGD or IMC referred to an American medical center for endoscopic treatment between 2004 – 2010. All patients had pre-treatment staging by EUS. We examined the frequency that EUS findings consistent with advanced disease (tumor invasion into the submucosa, lymph node involvement, or regional metastasis) led to a change in management. The analysis was stratified by nodularity and pre-EUS histology. RESULTS: 135 patients with HGD (n=106, 79%) or IMC (n=29, 21%) had staging by EUS (79 non-nodular, 56 nodular). Pathologic lymph nodes or metastases were not found by EUS. There were no endosonographic abnormalities noted in any patient with non-nodular mucosa (0/79). Abnormal EUS findings were present in 8/56 patients (14%) with nodular neoplasia (5 IMC, 3 HGD). EMR was performed in 44 patients with a nodule, with 13% (6/44) having invasive cancer. In nodular neoplasia, the EUS and EMR were abnormal in 24% (5/21) and 40% (6/15) of those with IMC and 9% (3/35) and 0% (0/29) of those with HGD, respectively. CONCLUSIONS: EUS did not alter management in patients with non-nodular HGD or IMC. Because the diagnostic utility of EUS in subjects with non-nodular BE is low, the value of performing EUS in this setting is questionable. For patients with nodular neoplasia, resection of the nodule with histologic examination had greater utility than staging by EUS.